Clinical Utility of Quantitative Hbsag in Chronic Hepatitis B Infection - Poernomo Boedi Setiawan; Ummi Maimunah; Khairu Zein (The Indonesian Society for Digestive Endoscopy, 2019)
The prevalence of hepatitis B infection in Indonesia is still alarming, while its therapies cannot eradicate the virus and only aim for long term viral suppression. HBsAg quantification has become an emphasis on researches, regarding its capacity to identify the natural history of hepatitis B virus infection and predict the outcome of therapies. This review aims to determine the clinical role of HBsAg in chronic hepatitis B infection by reviewing textbooks, journal articles, and review articles without language restriction. This review finds that HBsAg is capable of predicting degrees of liver fibrosis severity in patients with chronic hepatitis B infection. Furthermore, HBsAg quantification can be used to distinguish inactive carriers from patients with HBeAg-negative chronic hepatitis B. The decrease of HBsAg is a good predictor of HBsAg loss, and it denotes discontinuation of nucleoside/nucleotide analog therapy. HBsAg quantification is also used in combined PEG-IFN and nucleoside/nucleotide analog therapy. Nevertheless, this role is still controversial. Additionally, HBsAg cannot replace the major roles of HBV DNA measurement in therapy management. Using either HBsAg or HBV DNA in therapy algorithm decreases its predictive value, hence recommendation to use both. In identifying patients with occult hepatitis B infection (OBI), HBV DNA still cannot be replaced by HBsAg quantification. Furthermore, HBsAg quantification may not be a good predictor of hepatocellular carcinoma in patients with OBI. Future studies are expected to demonstrate the role of HBsAg in current hepatitis B therapy and also future therapies.